2022
DOI: 10.46827/ejsss.v7i3.1229
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Moral Decadence on Academic Performance Among Students in Tertiary Institutions of Anambra State, Nigeria

Abstract: The study examined the implication of moral decadence on the academic performance of students in tertiary institutions of Anambra State. The design of the study is a cross-sectional survey research design. Three research questions were formulated to form the study. The population of the study was 400 students. The population was made up of 8 tertiary institutions of learning in Anambra state which includes Nnnamdi Azikiwe University, Awka, Chukwuemeka Odumegwu Ojukwu University, Tansian University Umunya, Mado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dialectic behavior therapy therefore teaches people to peacefully and productively co-exist. Nnadi, et al (2020), in their work reported that assertiveness training could reduce social withdrawal behavior among adolescents. Manesh, et al (2015), and Adegoke (2018), agreed that social stress could cause social avoidance, negative feelings of social interactions and distress but assertiveness training skills aid the reduction of social anxiety, changes expectations, beliefs, attitude, and build positive evaluation among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Dialectic behavior therapy therefore teaches people to peacefully and productively co-exist. Nnadi, et al (2020), in their work reported that assertiveness training could reduce social withdrawal behavior among adolescents. Manesh, et al (2015), and Adegoke (2018), agreed that social stress could cause social avoidance, negative feelings of social interactions and distress but assertiveness training skills aid the reduction of social anxiety, changes expectations, beliefs, attitude, and build positive evaluation among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Though modification of undesirable behaviour in the classroom is equally dependent on the services of a well-motivated and committed counsellor (Chigbu, Nwobi, Ngwaka & Mokwelu, 2021).There was active classroom participation when the token economy was introduced (Boniecki & Moore, 2003). This simply means that disruptive behaviour showed a negative impact on academic performance among secondary students (Grace, Uzoekwe, Ofojebe & Chigbu, 2022). Studies have also shown that the token economy system has been effective in decreasing non-desiredbehaviour and increasing pro-academic behaviour in students (Robacker, Rivera & Warren in Wiolliamson & Mcfadzen, 2020).…”
mentioning
confidence: 99%